2006
DOI: 10.1002/arch.20113
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary origin of Venturia canescens virus‐like particles

Abstract: Insect host-parasitoid interactions provide fascinating examples of evolutionary adaptations in which the parasitoid employs a variety of measures and countermeasures to overcome the immune responses of its host. Maternal factors introduced by the female wasps during egg deposition play an important role in interfering with cellular and humoral components of the host's immune defence. Some of these components actively suppress host immune components and some are believed to confer protection for the developing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 62 publications
(79 reference statements)
0
18
0
Order By: Relevance
“…However, there might be a cost to the wasp for the replication of PDVs. Some wasps do not use PDVs at all, and the case of V. canescens [25,100] suggests reversal from PDV use could be possible. In this light, why are PDV genomes so large?…”
Section: (C) Evolutionary Model For Polydnavirus Genome Extensionmentioning
confidence: 99%
“…However, there might be a cost to the wasp for the replication of PDVs. Some wasps do not use PDVs at all, and the case of V. canescens [25,100] suggests reversal from PDV use could be possible. In this light, why are PDV genomes so large?…”
Section: (C) Evolutionary Model For Polydnavirus Genome Extensionmentioning
confidence: 99%
“…In the parasitized host, they protect the eggs against encapsulation, an insect immune response involving the engulfment of foreign bodies in a sheath of immune cells. Unlike polydnaviruses, which convey virulence genes, VLPs are devoid of DNA ( 10 , 11 ) and enclose virulence proteins ( 12 ). VLPs do not resemble the particles of known viruses, and a debate about whether these particles are truly of viral origin has raged since the early 1970s ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike polydnaviruses, which convey virulence genes, VLPs are devoid of DNA ( 10 , 11 ) and enclose virulence proteins ( 12 ). VLPs do not resemble the particles of known viruses, and a debate about whether these particles are truly of viral origin has raged since the early 1970s ( 12 ). We show here that VLPs are clearly of viral origin and consist of virulence proteins wrapped in viral envelopes.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, transcription of Glov, another antibacterial peptide was suppressed for 2 d after parasitization. It has been shown that several larval parasitoids are able to suppress immune responses of their hosts by injection of viruses, virus-like particles, or venom (Edson et al, 1981;Beckage, 1998;Strand and Pech, 1995;Zhang et al, 2004;Amaya et al, 2005;Reineke et al, 2006). Trichogramma species are known to inject a venom into host eggs (Strand 1986;Strand and Pech, 1995) that might suppress some host immune reactions.…”
Section: Discussionmentioning
confidence: 99%